Efficacy and safety of ensifentrine, a novel phosphodiesterase 3 and 4 inhibitor, in chronic obstructive pulmonary disease: A systematic review and meta-analysis - Eeshal Fatima (18255772) (2024)
Background We evaluated the efficacy and safety of Ensifentrine in COPD via a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods We performed a detailed literature search on Medline (via PubMed), Scopus, Google Scholar, and Cochrane on the basis of pre-specified eligibility criteria. We used Review Manager to calculate pooled mean differences (MD) and 95% Confidence Interval (CI) using a random effects model. The Cochrane's Risk of Bias 2 (RoB-2) tool was used to assess the risk of bias in the included RCTs. Results A total of 4 studies, consisting of 2020 patients, were included in the meta-analysis. The mean age ranged from 62.5 years to 65.5 years in the included studies. All the included studies were at low risk of bias. Ensifentrine 3 mg dose significantly improved the mean peak Forced Expiratory Volume-1 (FEV-1), morning trough FEV-1, TDI score, ERS score, and SGRQ-C score as compared to the placebo, yielding a pooled MD of 149.76 (95% CI, 127.9 to 171.6), 43.93 (95% CI, 23.82 to 64.05), 0.92 (95% CI, 0.64 to 1.21, −1.20 (95% CI, −1.99 to −0.40), and −1.92 (95% CI, −3.24 to −0.59), respectively. Conclusion Ensifentrine is associated with improvements in outcomes related to COPD symptoms such as peak FEV-1, morning trough FEV-1 and TDI in the patients suffering from this chronic disease. It is also associated with improved quality of life as seen by E-RS score and SGRQ-C score. Other Information Published in: Respiratory Investigation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.resinv.2024.12.012